Contact-Tracing Outcomes Among Household Contacts of Fully Vaccinated Coronavirus Disease 2019 (COVID-19) Patients: San Francisco, California, 29 January–2 July 2021. (20th December 2021) - Sachdev, Darpun D; Chew Ng, Rilene; Sankaran, Madeline; Ernst, Alexandra; Hernandez, Katherine T; Servellita, Venice; Sotomayor-Gonzalez, Alicia; Stoltey, Juliet; Cohen, Stephanie E; Nguyen, Trang Quyen; Chiu, Charles Y; Philip, Susan
Abstract: Background: The extent to which vaccinated persons diagnosed with coronavirus disease 2019 (COVID-19) can transmit to other vaccinated and unvaccinated persons is unclear. Methods: Using data from the San Francisco Department of Public Health, this report describes outcomes of household contact tracing during 29 January–2 July 2021, where fully vaccinated patients with COVID-19 were the index case in the household. Results: Among 248 fully vaccinated patients with breakthrough infections, 203 (82%) were symptomatic and 105 were identified as the index patient within their household. Among 179 named household contacts, 71 (40%) contacts tested, over half (56%) were fully vaccinated and the secondary attack rate was 28%. Overall transmission from a symptomatic fully vaccinated patient with breakthrough infection to household contacts was suspected in 14 of 105 (13%) of households. Viral genomic sequencing of samples from 44% of fully vaccinated patients showed that 82% of those sequenced were infected by a variant of concern or interest and 77% by a variant carrying mutation(s) associated with resistance to neutralizing antibodies. Conclusions: Transmission from fully vaccinated symptomatic index patients to vaccinated and unvaccinated household contacts can occur. Indoor face masking and timely testing of all household contacts should be considered when a household member receives a positive test result in order to identify and interrupt transmission chains. Abstract : Based on health department contact-tracing data, fully vaccinated people with symptoms can spread SARS-CoV-2 to their vaccinated and unvaccinated household contacts. Face masks should be considered in shared household spaces when any household member is infected or symptomatic.